Perancangan Sistem Informasi Penjualan Obat Berbasis Website Pada Apotek Sehat Farma - Wina Novita Br Bangun; Ricky Ramadhan Harahap; Nova mayasari (Jurnal Nasional Teknologi Komputer, 2026)
The advancement of information technology has encouraged pharmacies to adopt digital systems to support sales processes and data management more effectively. This study aims to design and develop a web-based drug sales information system for Sehat Farma Pharmacy by emphasizing the application of User Interface (UI) and User Experience (UX) principles. The research stages include user requirement identification, business process analysis, navigation structure design, wireframe and prototype development, database design, system implementation, as well as functional and user experience testing. The system was developed using PHP and MySQL. The main features include authentication, a dashboard, drug data management, customer and supplier management, sales and return transactions, e-prescriptions, inventory management, and sales reporting. The interface was designed to be simple, consistent, responsive, and easy to understand so that users can operate each function efficiently and minimize errors. The testing results show that all core features function according to user requirements. The implementation of UI/UX design also improves navigation, drug data searching, transaction recording, inventory monitoring, and structured report presentation. Therefore, the developed system can support the daily operations of Sehat Farma Pharmacy through an easy-to-use interface, a clear interaction flow, and more effective and efficient information management.